Love, death and storytelling - Pamuk, Orhan (New statesman (1996))
"The Book of One Thousand and One Nights", also known as "The Arabian Nights", is a marvel of eastern literature, a treasure chest of secret logic, in-jokes, richness, strangeness, impudence and vulgarity. Argues that, more profoundly than any other book, it shows us what life is made of. (Author abstract - amended)